IMPLEMENTASI PENDIDIKAN KARAKTER DALAM MENANAMKAN SIKAP RELIGIUS DI MIN NANJUNGAN KECAMATAN PINO RAYA KABUPATEN BENGKULU SELATAN - Pirman Joyo; Nan surto (UIN Fatmawati Sukarno Bengkulu, 2018)
The purpose of this research is to know the steps of implementation and implementation of character education in instilling students ‘religious attitude, as well as supporting and inhibiting factors to instill students’ religious attitude in MIN Nanjungan Pino Raya District, South Bengkulu Regency. The formulation of this research problem is how the character educa- tion steps in instilling students ‘religious attitude in MIN? how to implement character education in instilling students’ religious attitude in MIN? and supporting factors and barriers to instill the religious attitude of students in MIN Nanjungan Pino Sub Raya Bengkulu Selatan Regency? This research is a qualitative research with inductive analysis. The data collection of this research was conducted by direct researchers. Techniques used for data retrieval are observation, wawancara, documentation and checklist. The result of this research is character education is already present in the content in K.13 curriculum. The findings of researchers in this study: first step implementation implemented by MIN Nanjungan on character education in instilling the reli- gious attitude of their students by forming religious teachers. Religious coach is a teacher appointed by the head of a madrasah to coordinate religious activities. The special step taken in instilling students’ religious attitude is to create a control card. The card aims to control the prayer time of five children when the child is outside Madrasah. Both implementation of character edu- cation in instilling students’ religious attitude through intra and extracurricular. Intra-curricular through the learning approach in the classroom. Being extra-curricular through programs created by religious coaches